Spermatozoa ultrastructure in Sciaenidae and Polynemidae (Teleostei : Perciformes) with some consideration on Percoidei spermatozoa ultrastructure - Gusmao-Pompiani, P.; Oliveira, C.; Quagio-Grassiotto, I (Churchill Livingstone, 2005)
Spermatozoa ultrastructure was studied in five marines (Paralonchurus brasiliensis, Larimus breviceps, Cynoscion striatus, Micropogonias furnieri, Menticirrhus americanus, Umbrina coroides, Stellifer rastrifer), and one freshwater (Plagioscion squamosissimus) species of Sciaenidae and one species of Polynemidae (Polydactylus virginicus). The investigation revealed that, in all species, spermatozoa display a round head, a nucleus containing highly condensed, filamentous chromatin clusters, no acrosome, a short midpiece with a short cytoplasmic channel, and a flagellum showing the classic axoneme structure (9 + 2) and short irregular lateral fins. In Sciaenidae, the spermatozoa are type II, the flagellar axis is parallel to the nucleus, the lateral nuclear fossa is double arched, the centriolar complex is outside the nuclear fossa, the proximal centriole is anterior and perpendicular to the distal centriole, and no more than ten spherical (marine species) or elongate (freshwater species) mitochondria are observed. Polynemidae spermatozoa are of the intermediate type with the flagellar axis eccentric to the hemi-arc-shaped nucleus, and exhibit no nuclear fossa, the centriolar complex close to the upper nuclear end, the proximal centriole lateral and oblique to the distal centriole, and one large ring-shaped mitocondrion. The data available show that no characteristic is exclusively found in the spermatozoa of members of the Sciaenidae family when compared to other Percoidei with type II spermatozoa. However, three characteristics were exclusively found in Polynemidae: (1) the hemi-arched nucleus; the positioning of the centrioles; and (2) the ring-shaped mitocondrion. The interrelationships between Sciaenidae and Polynemidae as well as between these two families and other Percoidei are herein discussed. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: ultrastructure; sperm; fish; Teleostei; Sciaenidae; Polynemidae